The Effectiveness of Using Difa Tara Interactive Learning Media in Increasing Critical Reasoning Abilities and Independence in Science Subjects in Elementary Schools - Sumarsi Sumarsi; Ristiana Dyah Purwandari (Proceedings Series on Social Sciences & Humanities, 2025)
Teachers are less aware of and ignore the diversity of students, so that in the learning process they still use learning models that do not accommodate student diversity. This condition causes students to be less able to develop critical reasoning skills and independence. One way that can be done to respond to the characteristics and identify problems of diverse students is to implement differentiated learning strategies with the interactive learning media Difa Tara. This research aims to test the effectiveness of using Difa Tara Interactive Learning Media to increase critical reasoning abilities and independence in science subjects in elementary school. This research uses a quantitative approach to the Quasi-Experimental research type. Data collection techniques were carried out using tests and questionnaires. Data analysis techniques use instrument validity and reliability tests, normality and homogeneity tests as prerequisite tests. Test the hypothesis using the T test. The results of the research show that the Difa Tara Interactive Learning Media is effective for critical reasoning abilities and independence. It has been stated from the hypothesis test that the significant value is 0.000, which means that H0 is rejected and H1 is accepted.